Doubly-filled COMPs in Alpine varieties - Schallert, Oliver; Bidese, Ermenegildo (Language Typology and Universals, 2021)
Violations of the Doubly-filled COMP filter (DFCs), most notably in the context of embedded questions, can be observed in Germanic, Romance, and even Slavic varieties in the Alpine regions. Using the direct survey technique, we examine DFC-phenomena in several dialects of Southern Bavarian (including language islands) and the adjacent Italian regions (Venetian, Friulian, etc.) in order to check for relevant similarities as well as differences. Whereas there is some indication for a structural parallelism between Germanic and Romance in terms of the wh-items involved, both language groups are set apart when it comes to DFCs in root sentences.
CRIS-Team Scopus Importer:2024-10-21
Keywords: Alpine Sprachbund; doubly-filled COMP (filter); German dialects; Romance dialects; wh-dependencies